The art of conversation - Noyes, Hattie May (My University, 1891)
Introduction: Language is a gift of nature to man, by means of which he is enabled to express his thoughts and communicate them to his fellow men. This interchange of thought is called conversation. The use of this power is what we may understand by the art of conversation. Some persons have the ability to express their thoughts easier and to a greater extent than others, the words of the one flowing incessantly, while of the other they come sparingly and with effort. But however great the natural power of expression may be, that alone will not make a good talker. A person cannot go on talking forever without something to say, any more than a mill can continually turn out flour without wheat to grind. The art of conversation is said to be dying out; This may be due in a large measure to the constant reading of the present day. A book is read simply to say it has been read, and but little thought is bestowed upon it. If after we have read a book we would talk about what we have read, it would impress itself on our minds and furnish food for thought. The failure of great literary authors as Pope, Dryden, and Goldsmith in conversation was due to the fact that their thoughts were devoted entirely to writing and as deep thoughts do not lie near the surface, their ideas did not present themselves fast enough to be used in conversation.
Citation: Noyes, Hattie May. The art of conversation. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Language; Conversation; English; Speech; Theses; Manuscripts (documents)